2022
DOI: 10.2147/idr.s364279
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Predictors Among COVID-19 Elderly in Taif, Saudi Arabia

Abstract: Background: By December 2021, the COVID-19 pandemic had caused more than 266 million cases and 5 million deaths, especially among geriatric patients. Objective: To identify determinants of COVID-19-related death in geriatric patients. Methods: This is a comparative retrospective study involving 145 COVID-19 hospitalized patients who are more than 60 years old, conducted at King Faisal Medical Complex in Taif, Saudi Arabia, from June 2020 to August 2020. The main outcome studied was COVID-19-related death. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…After that, 300 articles were evaluated for full-text eligibility, and 197 articles with available data but not Asian were excluded. Ultimately, 103 studies conducted in Asia were enrolled in this meta-analysis [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Resultsmentioning
confidence: 99%
“…After that, 300 articles were evaluated for full-text eligibility, and 197 articles with available data but not Asian were excluded. Ultimately, 103 studies conducted in Asia were enrolled in this meta-analysis [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Resultsmentioning
confidence: 99%
“…However, the results concerning the relationship to hypertension remain inconsistent. Previous studies conducted in Marseille, France, and Taif, Saudi Arabia found no correlation between hypertension and heart disease and COVID-19-related deaths in elderly patients [ 15 , 24 ]. Another study concluded that heart disease was a significant predictor of higher COVID-19 mortality [ 25 ].…”
Section: Discussionmentioning
confidence: 99%